2006
DOI: 10.1074/jbc.m509584200
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Heparan Sulfate 6-O-Sulfotransferases in Human Embryonic Kidney 293 Cells Results in Increased N-Acetylglucosaminyl 6-O-Sulfation

Abstract: Heparan sulfate (HS) interacts with a variety of proteins and thus mediates numerous complex biological processes. These interactions critically depend on the patterns of O-sulfate groups within the HS chains that determine binding sites for proteins. In particular the distribution of 6-O-sulfated glucosamine residues influences binding and activity of HS-dependent signaling molecules. The protein binding domains of HS show large structural variability, potentially because of differential expression patterns o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 48 publications
(87 reference statements)
1
4
0
Order By: Relevance
“…This suggestion was supported by previous result that overexpression of 6-OST-1 increased the percentage composition of ΔHexUA-GlcNAc6S. 40) In conclusion, the present study shows the artificial control of sulfated structure of cell-surface HS by identifying the signaling pathway for 6-OST-1 for the first time. We found that L-M cells synthesized more 6-O-sulfated disaccharide units in HS in response to adrenaline.…”
Section: Discussionsupporting
confidence: 78%
“…This suggestion was supported by previous result that overexpression of 6-OST-1 increased the percentage composition of ΔHexUA-GlcNAc6S. 40) In conclusion, the present study shows the artificial control of sulfated structure of cell-surface HS by identifying the signaling pathway for 6-OST-1 for the first time. We found that L-M cells synthesized more 6-O-sulfated disaccharide units in HS in response to adrenaline.…”
Section: Discussionsupporting
confidence: 78%
“…This differential activity of mSulf1 and mSulf2 in the mSulf knock-out MEFs may have important biological implications. Indeed, it is important to note that although no mouse 6-Osulfotransferase knock-outs have yet been published, in vitro experiments suggest that individual isoforms are non-specific and complementary in their sites of action [29,30]. Therefore the predominant control of 6S patterning, as seen by binding ligands, is probably due to mSulf activity.…”
Section: Regulation Underlying 6s Patterningmentioning
confidence: 99%
“…At high concentration, this enzyme, which normally preferentially targets IdoA, will start to increase the 2- O- sulfation of GlcA residues, which are then no longer substrate for the C5-epi and thus cannot be converted back to IdoA [ 271 ]. Overexpression of 6-OSTs increased both GlcNS and GlcNAc 6- O- sulfation, but also reduced the total IdoA content, 2- O- sulfation and modified the distribution of the N- sulfated domains [ 272 ]. HS produced by C5-epi and 2-OST knockout animals are enriched in N- and 6- O- sulfation, which could suggest a compensation mechanism to overcome the loss of IdoA and 2- O- sulfate, but the underlying mechanism remains unknown [ 127 , 179 ].…”
Section: Discussionmentioning
confidence: 99%